Seasonal Shift in Climatic Limiting Factors on Tree Transpiration: Evidence from Sap Flow Observations at Alpine Treelines in Southeast Tibet - Liu, Xinsheng; Nie, Yuqin; Luo, Tianxiang; Yu, Jiehui; Shen, Wei; Zhang, Lin (Frontiers in Plant Science, 2016)
Alpine and northern treelines are primarily controlled by low temperatures. However, little is known about the impact of low soil temperature on tree transpiration at treelines. We aim to test the hypothesis that in cold-limited forests, the main limiting factors for tree transpiration switch from low soil temperature before summer solstice to atmospheric evaporative demand after summer solstice, which generally results in low transpiration in the early growing season. Sap flow, meteorological factors and predawn needle water potential were continuously monitored throughout one growing season across Smith fir (Abies georgei var. smithii) and juniper (Juniperus saltuaria) treelines in southeast Tibet. Sap flow started in early May and corresponded to a threshold mean air-temperature of 0 oC. Across tree species, transpiration was mainly limited by low soil temperature prior to the summer solstice but by vapor pressure deficit and solar radiation post-summer solstice, which was further confirmed on a daily scale. As a result, tree transpiration for both tree species was significantly reduced in the pre-summer solstice period as compared to post-summer solstice, resulting in a lower predawn needle water potential for Smith fir trees in the early growing season. Our data supported the hypothesis, suggesting that tree transpiration mainly responds to soil temperature variations in the early growing season. The results are important for understanding the hydrological response of cold-limited forest ecosystems to climate change.